Phenological Research Methods for Environmental and Climate Change Analysis - Hudson, Irene L.; Keatley, Marie R. (Springer Netherlands, 2010)
As climate change continues to dominate the international environmental agenda, phenology the study of the timing of recurring biological events has received increasing research attention, leading to an emerging consensus that phenology can be viewed as an early warning system for climate change impact. A multidisciplinary science involving many branches of ecology, geography and remote sensing, phenology to date has lacked a coherent methodological text. This new synthesis, including contributions from many of the worlds leading phenologists, therefore fills a critical gap in the current biological literature. Providing critiques of current methods, as well as detailing novel and emerging methodologies, the book, with its extensive suite of references, provides readers with an understanding of both the theoretical basis and the potential applications required to adopt and adapt new analytical and design methods. An invaluable source book for researchers and students in ecology and climate change science, the book also provides a useful reference for practitioners in a range of sectors, including human health, fisheries, forestry, agriculture and natural resource management.